2013
DOI: 10.1007/978-3-642-31857-3
|View full text |Cite
|
Sign up to set email alerts
|

GPR Remote Sensing in Archaeology

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. While the advice and information in this book are believed to be true and accurate at the date of publication, neither the authors nor the editors nor the publisher can accept any legal responsibility for any errors or omissions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
146
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(148 citation statements)
references
References 0 publications
1
146
0
1
Order By: Relevance
“…Many studies and investigations have demonstrated the highly significant role of GPR in searching for ancient buried remains (Conyers, 2004;Goodman & Piro, 2013). The GPR prospecting was carried out using an IDS Hi Mod system with a 600 MHz antenna.…”
Section: Gpr Data Acquisition and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies and investigations have demonstrated the highly significant role of GPR in searching for ancient buried remains (Conyers, 2004;Goodman & Piro, 2013). The GPR prospecting was carried out using an IDS Hi Mod system with a 600 MHz antenna.…”
Section: Gpr Data Acquisition and Processingmentioning
confidence: 99%
“…The data were subsequently processed using standard twodimensional processing techniques (Persico, 2014) adopting GPR-Slice 7.0 software (Goodman, 2013). The processing flow-chart consisted of the following steps: i) header editing to insert the geometrical information, ii) frequency filtering, iii) manual gain, to adjust the acquisition gain function and enhance the visibility of deeper anomalies, iv) customized background removal to attenuate the horizontal banding in the deeper part of the sections (ringing), performed by subtracting a 'local' average noise trace in different time ranges estimated from suitably selected time-distance windows with low signal content (this local subtraction procedure was necessary to avoid artefacts created by the classic subtraction of a 'global' average trace estimated from the entire section, due to the presence of zones with a very strong signal), v) estimation of the average electromagnetic wave velocity by hyperbola fitting, and vi) Kirchhoff migration, using a constant average velocity value of 0.07 m/ns.…”
Section: Gpr Data Acquisition and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach for visualizing 3D iso is the use of surface rendering, assembled from all processed radargrams (Zanzi and Valle, 1999;Goodman and Piro, 2013). In Fig.…”
Section: Gpr Data Processing and Analysismentioning
confidence: 99%
“…In particular, it is well known that electromagnetic interferences can have significant effects on Ground Penetrating Radar (GPR) data in some particular conditions [1]. In order to counteract them, the human operator can think of filtering the signal in a suitable way during the processing phase.…”
Section: Introductionmentioning
confidence: 99%